Constitution peculiarities of the five-layer structure of isomophically substituted phases of CaLn4−xLnIxTi5O17 type - Titov, Y. A.; Belyavina, N. M.; Markiv, V. Ya.; Slobodyanik, M. S.; Chumak, V. V. (Reports of the National Academy of Sciences of Ukraine, 2014)
The crystal layer of CaPr3GdTi5O17 perovskite-like structure (LPS) is determined by X-ray powder diffraction (sp. gr. P21/b, a = 0.7671(3) nm, b = 3.145(1) nm, c = 0.5444(2) nm, γ = 96.99(2)º, RB = 0.086). The basic details of the crystallochemical mechanism of isomorphic replacement of REE atoms in LPS CaLn4Ti5O17 are established. The character of the localization of Ca, Ln, and LnI atoms in LPS CaLn4−xLnIxTi5O17 does not depend on the symmetry of a crystal lattice. As for Ca and REE atoms, the partial ordering with primary localization of Ca atoms at the center and in the intermediate layers of perovskite-like blocks is typical. REE atoms are on the boundaries of blocks, and LnI atoms are orderly located only on the boundaries of blocks.